Rutting and moisture damage evaluation of warm mix asphalt incorporating POFA modified bitumen - Abdulrahman, S. (Blue Eyes Intelligence Engineering and Sciences Publication, 2019)
The unwanted disposal Palm Oil Fuel Ash (POFA) can be minimised through its application in road construction. Available literatures have shown that POFA improves the performance of hot mix asphalt (HMA), however, its application in warm mix asphalt (WMA) remains unexplored. This study was carried out to investigate the performance of WMA with POFA modified bitumen. In this study, Five percent POFA and 0.75 Evotherm is blended with 60/70 PEN grade bitumen to produce warm POFA modified bitumen (B3). The B3 binder is subjected Fourier Transform Infrared spectroscopy (FTIR), Atomic Force Microscopy (AFM), and Contact angle measurements to understand the effect of this modification at microstructural level. Also, the binder is used in preparing dense graded asphalt concrete (AC14) at 140/130 â mixing/compaction temperatures rspectively. Mixture performance tests such as Marshall flow and stability, dynamic creep, Asphalt Pavement Analyser (APA), tensile strength ratio, and boiling water tests were used to examine the resistance of B3 binder to rutting and moisture damage. Results from dynamic creep and APA test shows that the WMA mixtures possess 30 improved rutting resistance than the conventional HMA. On the contrary, the WMA sample parade lower resistance to moisture damage by 10 as revealed by the tensile strength ratio test. All the tested samples satisfied the specification limits for AC14 mixture, thus alleviating any concern regarding the moisture damage vulnerability of WMA mixtures. Â© BEIESP.